2015
DOI: 10.1185/03007995.2015.1074065
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac autonomic dysfunction in elderly women with myocardial infarction

Abstract: This study suggests that elderly women with MI may have a worse prognosis than men, indicated by cardiac autonomic dysfunction. Since our study is cross-sectional and cannot infer causality, causation should be confirmed in further longitudinal studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Our HRV findings indicate that women have poorer autonomic functioning at 1 and 12 months following ACS, compared to men. These findings are consistent with those of De Oliveira Pinheiro and colleagues who reported that compared to men, women had lower HRV (triangular index, SDNN, HF, HF/LF, RMSSD and SD1) in the immediate 5-10 days following MI [11]. Indeed, our findings indicate that such differences persist after the acute period.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our HRV findings indicate that women have poorer autonomic functioning at 1 and 12 months following ACS, compared to men. These findings are consistent with those of De Oliveira Pinheiro and colleagues who reported that compared to men, women had lower HRV (triangular index, SDNN, HF, HF/LF, RMSSD and SD1) in the immediate 5-10 days following MI [11]. Indeed, our findings indicate that such differences persist after the acute period.…”
Section: Discussionsupporting
confidence: 93%
“…To date, only one study has investigated sex differences in HRV following ACS. De Oliveira Pinheiro et al found that women over 50 years of age had significantly reduced HRV compared to agematched men, 5-10 days post-infarction [11]. No study has yet examined whether this sex-specific differential exists beyond the initial weeks following ACS.…”
Section: Introductionmentioning
confidence: 99%
“…In women, estrogen can protect women against heart disease by reducing circulatory levels of harmful cholesterol [58], whereas testosterone increased the concentrations of low-density lipoprotein and inflammatory markers that can drive the progression of atherosclerosis and stroke [59][60][61] in men. Further, there is evidence that women have stronger immune systems, in part because testosterone caused immunosuppression and more frequently infection [60,62]. From a psychological perspective, women who provide more social support to others and are more engaged in their social networks are shown to be buffered or at least better equipped to deal with stress.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial ischemia induces changes in the neurohumoral control systems, including sympathoexcitation, that contribute to autonomic nervous system (ANS) imbalance and myocardial remodeling[1, 2] [3]. Cardiac ANS is comprised of the intrinsic and extrinsic networks of the cardiac neural circuits that closely control cardiac function [46].…”
Section: Introductionmentioning
confidence: 99%
“…In the diseased heart, there is evidence that abnormal autonomic function can lead to and exacerbate congestive heart failure, ventricular arrhythmias, and sudden cardiac death [1, 2] [3]. Clinically, inhibition of the sympathetic ANS through neural modulation techniques such as thoracic epidural anesthesia, spinal cord stimulation, and stellate ganglion sympathectomy, has been shown to be beneficial in treating ventricular arrhythmias[1721].…”
Section: Introductionmentioning
confidence: 99%